1990
DOI: 10.1089/clm.1990.8.31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with a New Pulsed Dye Laser for Ureteral Stone Lithotripsy

Abstract: Forty-five patients with 46 ureteral stones were treated using a new pulsed dye laser (Pulsolith, TMI). A fiber of 250 micrometers was used through rigid (40 cases) or flexible (6 cases) ureteroscopes. Stones were located in the upper third (5 cases), middle third (5 cases), or lower third (36 cases) of the ureter. Stone composition was calcium oxalate dihydrate or monohydrate, struvite, or uric acid in 34, 7, 2, and 2 patients, respectively. Thirty-six stones (78%) were fragmented, including 14 cases that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Accord ing to the reports of quite a few centers, laser lithotripsy can be regarded as an attractive alternative method of lithotripsy with a low rate of complications [ 18,19], In contrast to rigid ureteroscopes, curvatures of the ureter can be more easily overcome by flexible uretero scopes especially if there are fixations of the ureter. Fur thermore, the complete pyelocaliceal space can be in spected.…”
Section: Discussionmentioning
confidence: 99%
“…Accord ing to the reports of quite a few centers, laser lithotripsy can be regarded as an attractive alternative method of lithotripsy with a low rate of complications [ 18,19], In contrast to rigid ureteroscopes, curvatures of the ureter can be more easily overcome by flexible uretero scopes especially if there are fixations of the ureter. Fur thermore, the complete pyelocaliceal space can be in spected.…”
Section: Discussionmentioning
confidence: 99%
“…However, from the aspect of efficacy of lithotripsy by Ho:YAG laser, lithotripsy was achieved in all 102 (100%) lithotripsy procedures, which included PNL and vesicolithotripsy. Conversely, the pulsed dye laser had an efficacy rate of 78-98% for lithotripsy [14,15,21,22]. The final effect in our patients treated by TUL using the Ho:YAG laser was 92% efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…The pulsed dye laser has a wavelength of 504 nm that is selectively absorbed by black or brown, which is the color of many urinary tract stones. Therefore, it is ineffective for so-called pale stones such as a cystine stone [14,15]. Conversely, the Ho:YAG laser has a wavelength of 2,100 nm, which can be absorbed to a large extent by water; hence, the laser beam can be absorbed by water present in the micropores on the stone surface, producing an effect irrespective of the color of the stone.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical use, the pulsed dye laser has been found to be safe and effective in treating ureteral calculi. Various authors have reported clinically successful ureteral stone fragmentation in 78-88% of patients treated [8][9][10]. In an early series using the pulsed dye laser with an 11.5 Fr.…”
Section: Discussionmentioning
confidence: 99%